2012
DOI: 10.1111/j.1474-9726.2012.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose delays age‐dependent proteotoxicity

Abstract: Nutrient availability influences an organism’s life history with profound effects on metabolism and lifespan. The association between a healthy lifespan and metabolism is incompletely understood, but a central factor is glucose metabolism. Although glucose is an important cellular energy source, glucose restriction is associated with extended lifespan in simple animals and a reduced incidence of age-dependent pathologies in humans. We report here that glucose enrichment delays mutant polyglutamine, TDP-43, FUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
46
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 41 publications
8
46
3
Order By: Relevance
“…It has previously been reported that sugar can have a detrimental effect on aging (Lee et al, 2009;Schlotterer et al, 2009;Schulz et al, 2007;Tauffenberger et al, 2012). Here, we have observed a similar detrimental effect at the higher concentrations tested (above 1% of glucose) and on non-proliferating E. coli.…”
Section: Mechanisms Ofsupporting
confidence: 75%
See 2 more Smart Citations
“…It has previously been reported that sugar can have a detrimental effect on aging (Lee et al, 2009;Schlotterer et al, 2009;Schulz et al, 2007;Tauffenberger et al, 2012). Here, we have observed a similar detrimental effect at the higher concentrations tested (above 1% of glucose) and on non-proliferating E. coli.…”
Section: Mechanisms Ofsupporting
confidence: 75%
“…3A, Table S3). On the contrary, animals growing under this low concentration of sugar live shorter than those feeding on a sugar free medium, indicating a deleterious effect of the sugar for the longevity of the nematodes as has been described before (Lee et al, 2009;Schlotterer et al, 2009;Schulz et al, 2007;Tauffenberger et al, 2012) and here at higher concentration of sugars. Additionally, no increase in longevity is observed when animals fed UV-treated E. coli in the presence of 0.1% sugar (Supplementary data, Fig.…”
Section: Mechanisms Ofmentioning
confidence: 66%
See 1 more Smart Citation
“…Surprisingly, CaI reduced oligomerization of Aβ in control worms that expressed Aβ, but in which the dld-1 gene was not suppressed by RNAi. Matching results were also reported by Tauffenberger et al [506] where high glucose concentrations protect against Aβ-mediated paralysis but simultaneously induced the formation of toxic oligomers of Aβ. Overall, the protective effect of MICA seems to occur through inhibition of Aβ oligomerization, which can be modulated through calcium signaling.…”
Section: Discussionsupporting
confidence: 88%
“…We found that either 1% glucose or 1% glycerol alleviated paralysis in Aβ transgenic worms. Tauffenberger et al [506] previously found the same result for glucose in worms and suggested that glucose enrichment protects against Aβ proteotoxicity and neurodegeneration. Our results are consistent with this interpretation for both glucose and glycerol.…”
Section: Discussionsupporting
confidence: 54%